2009
DOI: 10.2165/11317650-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Visual Field Loss in Patients with Refractory Partial Epilepsy Treated with Vigabatrin

Abstract: Since the probability of VAVFL is positively associated with treatment duration, careful assessment of the risk-benefit ratio of continuing treatment with vigabatrin is recommended in patients currently receiving this drug. All patients continuing to receive vigabatrin should undergo visual field examination at least every 6 months for the duration of treatment. We recommend two-level (three-zone), gradient-adapted, suprathreshold static perimetry of the peripheral field together with threshold perimetry of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
56
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 36 publications
3
56
0
2
Order By: Relevance
“…Nevertheless, severe visual field constriction to <30° of retained monocular temporal visual field, corresponding to a total extent of binocular vision of <60°, occurred in 2% of patients. In spite of the differences between the analyses, Wild and colleagues (Wild et al, 2009) found that 15 of 386 patients (4%) in Groups I and II had severe vigabatrin-attributed visual field loss, which is similar to the findings of our present analysis. However, in contrast to the analysis of Wild and colleagues (Wild et al, 2009), we found a weak correlation between answering "yes" to at least 1 question on the visual function questionnaire and severity of the visual field defect.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Nevertheless, severe visual field constriction to <30° of retained monocular temporal visual field, corresponding to a total extent of binocular vision of <60°, occurred in 2% of patients. In spite of the differences between the analyses, Wild and colleagues (Wild et al, 2009) found that 15 of 386 patients (4%) in Groups I and II had severe vigabatrin-attributed visual field loss, which is similar to the findings of our present analysis. However, in contrast to the analysis of Wild and colleagues (Wild et al, 2009), we found a weak correlation between answering "yes" to at least 1 question on the visual function questionnaire and severity of the visual field defect.…”
Section: Discussionsupporting
confidence: 89%
“…The current paper complements the previously published analysis of this same study (Wild et al, 2009). This analysis employed quantitative measurements of the visual field along the horizontal meridian from kinetic perimetry to estimate the severity of visual field defects.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Эти исследования проде-монстрировали, что вигабатрин эффективен в лече-нии инфантильных спазмов в большинстве случаев независимо от их этиологии, но все же наибольшую эффективность данный препарат продемонстрировал у пациентов с туберозным склерозом. Вигабатрин, как правило, хорошо переносился, однако его исполь-зование было связано с нарушением периферического зрения у части пациентов [21]. По данным американ-ских исследователей, у детей с туберозным склерозом вигабатрин следует рассматривать в качестве препа-рата начальной терапии инфантильных спазмов [11].…”
unclassified